Implementation of Joint Program Protect Children in The Protection of Child Victims of Violence at The Women's Empowerment Service of Child Protection and Family Planning, Sidoarjo Regency - Bastian, Moch Aril; Tukiman, Tukiman (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
Child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with the dignity of humanity, and get protection from violence and discrimination. The diamond program is one of the efforts of DP3AKB Sidoarjo Regency in preventing violence against children. The Diamond Program focuses on Violence Protection activities at the school level. to optimize the Diamond Program. To find out the implementation of the Diamond program in providing protection for victims of violence by the Sidoarjo Regency DP3AKB, it refers to the focus of research according to Edwards III on factors that influence the implementation of public policies consisting of four indicators, namely: communication, resources, disposition and bureaucratic structure. This study aims to describe the implementation of the Diamond program in providing protection for victims of child abuse at the Sidoarjo Regency DP3AKB. This research method is a qualitative approach. Data were obtained through observation, interviews and documentation. The results showed that the implementation of the program using the Edwards III model consisted of communication factors, resources, disposition, and bureaucratic structure, and the results were quite good although not satisfactory. This program has not yet been achieved to solve the problem of sexual violence against children. This is due to the fact that there are still many schools that have not received program counseling given the limited budget owned by DP3AKB. However, the existence of this Diamond program shows achievements with the commitment of the Sidoarjo Regency Government regarding the rampant sexual violence as evidenced by the high number of sexual violence cases through the formation of the PPA Task Force which involves synergy between related agencies and OPD.